(untitled) - Dungan, Nathan (New York, 2003)
Praise for Prodigal Sons & Material Girls "Nathan Dungan's book is for every parent, regardless of wealth or status-it will be the go-to book for a good long time. Its messages about money and values are timeless, and right on time." -Harvey MacKay Bestselling author of Swim With the Sharks Without Being Eaten Alive and Dig Your Well Before You're Thirsty, among other titles "For harassed parents and manipulated children, Nathan Dungan's book provides a powerful protective shield. I especially appreciated his ‘Share-Save-Spend' approach, with its emphasis on teaching children the importance of sharing with those less fortunate. It's a lesson that can help all of us, not only our children, live within our means and make the world a better place." -John de Graaf coauthor, Affluenza: The All-Consuming Epidemic coproducer of the PBS Affluenza series "Nathan Dungan has written a gem. He explains in a clear and engaging way how Madison Avenue has our kids in their cross hairs. What's even better though is that he gives sound and practical advice about what we can do about it. I urge everyone who cares about kids to read this book." -David Walsh, PhD President, National Institute on Media and the Family "Nathan Dungan exposes the culture of spending that victimizes our children and young people. Nathan helps us learn to lead the young people we care about toward more satisfying values and behaviors. Parents, grandparents, and mentors to the next generation will find this book a must." -Rev. Loren B. Mead Founding President, The Alban Institute "Prodigal Sons and Material Girls is a wake-up call to one of the biggest problems facing kids today: the inability to deal responsibly with money. Mr. Dungan's practical advice is to reorder our financial priorities . . . to share first, save next, and spend later . . . and then to pass these values on to our children. Only by doing so will we successfully defeat the three-headed monster of consumer products companies, media conglomerates, and advertising agencies." -Bruce Nicholson President and CEO, Thrivent Financial for Lutherans A portion of the author's proceeds will be donated to charitable causes.
Keywords: Parents,Children,Cha mẹ,Trẻ em; Finance, Personal,Finance, Personal,Tài chính, cá nhân,Tài chính, cá nhân